Preparation and properties of co-mixed crystals of 1,3-di- and 1,3,5-triamino- 2,4,6-trinitrobenzenes with attractive cyclic nitramines - Patil, Veerabhadragouda B.; Bělina, Petr; Trzcinski, Waldemar; Zeman, Svatopluk (My University, 2022)
Co-agglomeration was used to prepare co-mixed crystals of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) with RDX, b-HMX, BCHMX and e-CL-20. The molecular rearrangements in mixed crystals were verified using Raman, FTIR, and PXRD techniques. The significant stretching vibrations indicated that the resultant co-agglomerates (CACs) are co-crystals (CCs), where HMX appears in its d-modification and CL-20 in its b-modification. Logical relationships, described already for the 1,3-diamino-2,4,6-trinitrobenzene (DATB) CACs, between some FTIR and Raman vibrational modes and parameters of their initiation and detonation, after extending with the data for the TATB analogues, produced greater predictability. The densities of TATB CACs are higher than those of the pure nitramines (including b-CL-20). An evaluation of the dependence of the impact sensitivity on the performance or energy content in the DATB and TATB CACs is consistent with the Licht’s rule with some exceptions for DATB and an unambiguous relationship for the use of the heat of combustion as a representative of performance for TATB. This sensitivity is quite strongly reduced in the TATB CACs compared to their DATB analogues. The detonation energies of the DATB and TATB CACs are higher than would be expected from the percentage of coformers in them. Among the CACs studied, the most interesting appears to be HMX/TATB, which has a density slightly greater than pure HMX, with only slightly reduced detonation parameters, while its impact resistance is extremely high.
Příprava a vlastnosti směsných krystalů 1,3-di- a 1,3,5-triamino- 2,4,6-trinitrobenzenů s atraktivními cyklickými nitraminy
Keywords: detonation; co-crystals; co-agglomeration; impact sensitivity; nitramines; detonace; kokrystaly; koaglomerace; nárazová citlivost; nitraminy